(untitled) (Vietnam Journal of Community Medicine, 2025)
Objective: To describe the clinical and paraclinical features and to assess the tympanoplasty with microscopic extended endaural approach of chronic otitis media patients with ear canal stenosis in Ear Nose Throat Department, Viet Tiep Friendship Hospital, Hai Phong from 1/2023 to 12/2023. Methods: A cross-sectional study was conducted on 28 patients with chronic otitis media at Viet Tiep Friendship Hospital who underwent tympanoplasty using extended endoscopic method through the endotympanic route. Results: 50% of patients were hospitalized for ear discharge, of which 57.1% had mucopurulent ear discharge; 35.7% of patients had central tympanic membrane perforation, of which 85.7% had smooth perforation margin; 67.9% had bright intramastoid bright on computed tomography scans. After surgery, 100% of patients had closed tympanic membrane post surgery, and hearing loss symptoms were significantly improved. Before surgery, 82.1% of patients had hearing loss, and after surgery, this rate was 17.9%. Conclusion: 100% of patients had closed tympanic membrane closure, the rate of hearing loss patients improved significantly after surgery from 82.1% to 17.9%.